Metodika práce s žáky se specifickými poruchami učení: Aplikace písní s rytmickým a pohybovým doprovodem v cizím jazyce (francouzština) Metodická příručka - Schejbalová, Zdeňka (Masaryk University Press, 2020)
Title in English: The Methodology of Classroom Management of Pupils with Specific Learning Difficulties: Songs Application with Rhythmical and Movement Supplement in the Foreign Language (French): Methodical Manual The methodological manual is intended to facilitate the acquisition of a foreign language (French) by pupils with specific learning disabilities. Choral singing, recitation and accompanying playing rhythmic instruments, or movement and dance contribute to the removal of barriers and shyness between pupils with SLD and intact pupils, strengthening the overall cooperation between pupils, developing speech skills and language skills, communication in a foreign language, strengthening the socio-emotional competencies of pupils in both groups through aesthetic and emotional experiences from joint activities. The manual is divided into a theoretical part and an appendix, which contains methodological and practical sheets.